Fortsatt gran eller självföryngrad björk efter stormfällning? : en ekonomisk analys - Hansson, Olof (SLU/Southern Swedish Forest Research Centre, 2002)
The southern part of Sweden, Skåne, is frequently exposed to storms causing great damage to Norway spruce (Picea abies L. Karst.) stands. A storm during the winter 1999/2000 raised the attention of the problem. A lot of forest owners got large areas of spruce stands wind thrown during this storm. Can naturally regenerated birch (Betula sp.) be an alternative on these wind-exposed sites? This was the main question I was facing when discussilig the problems with Esben Möller Madsen, Söderåsens forest district. The aim of this master thesis was to present an economic analysis of Norway spruce versus birch. The analysis was based on soil value calculations of different cultivation models and changes in the future. The work was based on both a literature study and measurements in naturally regenerated birch stands. The results from the measurements were used as input data in a yield model in order to predict the growth. The yield prognoses together with the literature study as well as data from the Forest district were used for the economic analysis. One of the conclusions was that birch, although having a bad reputation, showed a better economic result than expected, but with the price level of today, Norway spruce was more profitable. However the rate of interest played a major roll in the choice between spruce and birch. A low interest rate favoured spruce with a higher initial investment, while birch with a low initial investment was favoured by a high interest rate. Another conclusion was that a small change of the price level would have a big impact on the economic result.